AB0478 Influences of Disease Activity at Initiation of Iguratimod, A Small-Molecule Antirheumatic Drug, on Efficacy of Iguratimod in Patients with Rheumatoid Arthritis: A Multicenter Study. (10th June 2014) - Hirano, Y.; Kanayama, Y.; Yoshioka, Y.; Kanda, H.; Kaneko, A.; Kojima, T.; Ishiguro, N.
Abstract : Background: Iguratimod (IGU), known as T-614, is a small-molecule antirheumatic drug developed in Japan and used in Japanese clinical practice since June in 2012. IGU is known to inhibit nuclear factor-kappa B activation in cultured human synovial cells 1 . Although biological agents (BIO) have good efficacy to treat rheumatoid arthritis (RA), they costs very much. IGU is comparatively cheap and used as monotherapy or combination therapy with methotrexate (MTX) in Japan. Data in clinical practice is lacking and necessary. Objectives: This retrospective study investigated efficacy of IGU in RA patients with focus on disease activity at initiation of IGU using data from the Japanese multicenter registry (TBCR). Methods: 34 cases (29 female and 5 male) with RA from 9 institutes in Japan were included. These patients were divided into two groups (high disease activity group; HG and moderate and low disease activity group; MLG) using DAS28-CRP at initiation of IGU. 17 cases were included in HG and 17 cases were included in MLG. Patients' characteristics, time course of disease activity, drug retention rate at 24 weeks and change value in disease activity parameter s from 0w to 24w were compared with each other. Results: Mean age was 67.3 years old in HG and 65.5 years old in MLG. Mean RA duration was 119.8 months in HG and 169.7 months in MLG. MTX use rate was significantly low in HG compared with in MLG (35.3% vs. 76.5%, p=0.037). Mean dose of MTX used was 2.9mg/w in HG and 5.7mg/w in MLG. Mean DAS28-CRP at 0, 4, 8, 12 and 24w was 5.23, 4.64, 4.41, 4.21 and 3.60 in HG and 3.20, 3.22, 3.01, 2.90 and 2.65 in MLG. DAS28-CRP was significantly decreased in only HG. Same finding was observed in SDAI. Drug retention rates at 24w were 70.6% in HG and 88.2% in MLG (not significant). Delta DAS28-CRP from 0w to 24w were 1.77 in HG and 0.58 in MLG (p=0.03). Delta SDAI were 16.1 in HG and 3.5 in MLG (p=0.03). There were significant differences in delta tender joints counts, general VAS and ESR between two groups and better improvement was seen in HG than MLG. Conclusions: More treatment options other than sufficient MTX and BIO are needed in RA patients with concomitant disease such as lung disease or renal dysfunction. High cost of BIO is another issue to inhibit improvement of signs and symptoms in RA patients. This study suggests that IGU is one of the options not only in RA patients treated with sufficient MTX but also in RA patients with high disease activity treated with insufficient MTX. References: M. Kohno et al. Inhibitory effect of T-614 on tumor necrosis factor-alpha induced cytokine production and nuclear factor-kappa B activation in cultured human synovial cells. J Rheumatol. 2001; 28(12): 2591-6. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2919